A Comparative Study of Democratic (Participative) And Laissez-Faire (Delegative) Leadership Styles in Enhancing Employee Retention in Higher Educational Institutions Across Major Cities of Gujarat - Ramesh Babu Anumolu; Dr. Ankita Jain (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Faculty retention is a critical factor in ensuring the stability, quality, and long-term success of higher educational institutions. Leadership styles play a significant role in shaping faculty satisfaction, engagement, and commitment to an institution. This study explores the impact of democratic (participative) leadership and laissez-faire (delegative) leadership on faculty retention in higher educational institutions across major cities in Gujarat. Through a quantitative research approach, data was collected from 120 faculty members using a structured Likert scale questionnaire measuring leadership perception, job satisfaction, and retention. Statistical analysis, including descriptive statistics, reliability testing (Cronbach’s Alpha = 0.721), correlation analysis, and regression modeling, was performed to evaluate the relationships between leadership styles and faculty retention. The findings indicate that democratic leadership has a strong and significant positive influence on faculty retention (p < 0.001), as leaders who encourage participation, provide transparent communication, and support faculty development create a more engaging and committed academic workforce. Conversely, laissez-faire leadership did not show a statistically significant impact on retention (p = 0.686), suggesting that while some faculty members appreciate autonomy, excessive independence without guidance may lead to disengagement. The study concludes that democratic leadership is a key determinant of faculty retention and recommends that higher education institutions implement inclusive decision-making, leadership training programs, and faculty engagement strategies to improve long-term retention. Furthermore, stakeholders such as university administrators, policymakers, HR departments, and faculty members should collaborate to create a supportive academic environment that promotes faculty satisfaction and career growth. The research highlights the need for structured leadership approaches to reduce faculty turnover and enhance institutional performance.
Keywords: Democratic; Laissez-Faire; Leadership Styles; Employee Retention In Higher Educational